Idiopathic hopping‐like forelimb lameness syndrome in ridden horses: 46 horses (2002–2014). (24th July 2015) - Dyson, S.; Rasotto, R.
Summary: There has been no analysis of a hopping‐type forelimb lameness syndrome seen in ridden horses. The objectives of this retrospective study were to describe the clinical features of this syndrome, response to diagnostic analgesia and imaging findings and to document post mortem findings. Clinical records from 2002 to 2014 were reviewed and data concerning signalment, history, lame limb(s), lameness characteristics, response to diagnostic analgesia and diagnostic imaging were recorded. There were 46 horses from 4 to 13 years of age, 6 of which had a history of known or suspected trauma immediately before the onset of reduced performance or lameness. Lameness seen when ridden was characterised by an intermittent shortened cranial phase of the step of the lame forelimb at the trot and marked elevation of the head as the affected limb was protracted, with the horse appearing to 'hop' (on the contralateral limb) as if trying to break to canter. When lameness was at its worst horses were unwilling to trot. Three horses showed sporadic severe stumbling. Local analgesia of the affected limb did not improve the lameness and in 16 horses lameness deteriorated. Three of 5 horses showed some improvement (≥2/8 grades) in the hopping‐type lameness after intra‐articular analgesia of the articular process joints of the sixth and seventh cervical vertebrae, ipsilateral to the lame forelimb. Radiographic, ultrasonographic and nuclear scintigraphic examinations were inconclusive. Two of 4 horses responded to treatment with gabapentin. In 3 horses post mortem examination revealed mild lymphocytic inflammation within or around the dorsal root ganglia of the fifth and sixth cervical nerve roots, sixth cervical nerve root or second thoracic nerve root ipsilateral to the lame limb. Idiopathic hopping‐type lameness syndrome in ridden horses may be a pain‐related condition ± a neurological component and currently has a guarded prognosis.